Maria Quitéria: o Movimento Feminino pela Anistia e sua imprensa (1975-1979) - Carboni, Maria Cecília Conte (2008)
The objective of this article is to analyze all the trajectory of Feminism Movement for the Amnesty (Movimento Feminino pela Anistia), through its periodical called Maria Quitéria, from 1977 to 1979. During its publishing, the periodical was dinamyze as a instrument of articulation of MFPA in a time of strong debate for a amnesty law for political prisoners and exiled, throughout the Brazilian military dictatorship, from 1964 to 1988. Its editorial line had a focus on the approval of the Amnesty law, with the particularity to present the theme under a feminine view, but not feminist one. The project its about its editorial line and the communication and action net that it is build around the periodical, and still analyze its propositions, strategically and its differentials dimensions of amnesty existents in the groups that formed the campain for amnesty